Formulation and evaluation of Ketoconazole niosomal gel drug delivery system - Shirsand, SB; Para, MS; Nagendrakumar, D; Kanani, KM; Keerthy, D (International Journal of Pharmaceutical Investigation)
Purpose: Niosomes play an increasingly important role in drug delivery as they can reduce toxicity and modify pharmacokinetic and bio-availability. Topically applied niosomes can increase the residence time of drugs in the stratum corneum and epidermis, while reducing the systemic absorption of the drug. It can act as drug containing reservoirs and the modification of the vesicular compositions or surface properties can adjust the drug release rate and the affinity for the target site. Ketoconazole is a broad spectrum Imidazole derivative useful in the treatment of superficial and systemic fungal infections. Materials and Methods: In order to improve the low skin penetration and to minimize the side effects associated with topical conventional drug administration, Ketoconazole niosomes were prepared by a thin film hydration method using different ratios of non-ionic surfactants (Span 40, 60 and Tween 60) along with cholesterol (CHO). The formulations were evaluated for size, shape, entrapment efficiency and in vitro drug release. Results: Niosomes appeared spherical in shape and size range was found to be 4.86 ± 1.24-7.38 ± 3.64 µm. The entrapment efficiency was found in the range of 55.14 ± 2.29-78.63 ± 0.91% and in vitro drug release in the range of 46.63 ± 0.95-72.37 ± 0.59% in 24 h. Ketoconazole niosomes formulated with Span 60 and CHO in the ratio of 1:0.2 were found to be promising and were incorporated into 1% Carbopol gel. The formulated gel was evaluated for various physicochemical parameters and antifungal activity. The in vitro drug release study was carried out using phosphate buffer saline pH 7.4 and was found to be 36.18 ± 1.50% in 12 h. Conclusion: Gel formulation containing niosomes loaded with Ketoconazole showed prolonged action than formulations containing Ketoconazole in non-niosomal form and it can be developed successfully to improve the antifungal activity.
Keywords: Ketoconazole; in vitro drug release studies; niosomes; skin permeation